TOCOPHEROLS AND 6-HYDROXY-CHROMAN-2-CARBONITRILE DERIVATIVES INHIBIT VASCULAR SMOOTH-MUSCLE CELL-PROLIFERATION BY A NONANTIOXIDANT MECHANISM - KARTAL ÖZER, NESRİN (ACADEMIC PRESS INC JNL-COMP SUBSCRIPTIONS, 1995)
The effects of two groups of similar compounds, a series of tocopherols and one of 6-hydroxy-chroman-2-carbonitrile, have been studied in vascular smooth muscle cells. A poor correlation has been found between antiproliferative and antioxidant properties of these molecules, D-alpha-Tocopherol inhibits cell proliferation, while D-alpha-tocopherylquinone has been found neither to inhibit nor to activate, D-beta-Tocopherol, a poor inhibitor of smooth muscle cell proliferation, has been shown to be capable of preventing and reversing the inhibition by D-alpha-tocopherol. It is concluded that the tocopherols and carbonitrile derivatives tested here appear to inhibit smooth muscle cell proliferation by a nonantioxidant mechanism, The competition between D-alpha-tocopherol and D-beta-tocopherol suggests the existence of a common binding site for the two molecules. (C) 1995 Academic Press,Inc.
Keywords: TOCOPHEROLS; SMOOTH MUSCLE CELL; PROLIFERATION; ANTIOXIDANT; ARTERIOSCLEROSIS; PROTEIN-KINASE-C; LOW-DENSITY-LIPOPROTEIN; HERITABLE HYPERLIPIDEMIC RABBIT; OXYGEN-FREE-RADICALS; DNA-BINDING ACTIVITY; ALPHA-TOCOPHEROL; VITAMIN-E; KAPPA-B; GROWTH-CHARACTERISTICS; RESTENOSING LESIONS